THE ROLE OF JOB SATISFACTION ON THE RELATIONSHIP BETWEEN SELF-LEADERSHIP AND ORGANIZATIONAL CITZENSHIP BEHAVIOR - MANSUR, AHSAN (JOURNAL OF RESEARCH IN MANAGEMENT, 2019)
Organizational citizenship behavior is a voluntary action carried out outside of its main dutyas an employee. Several factors can influence OCB attitudes, such as self leadership andjob satisfaction. The purpose of this study was to determine the effect of self leadership tojob satisfaction and organizational citizenship behavior in the organization or the company.The method used is a survey with the number of respondents in this study as many as 32respondents. The analysis used is the test of validity, reliability test, multiple regression,sobel test, and hypothesis testing. The results of the study show that job satisfaction canmediate between self leadership and organizational citizenship behavior